Evaluation of dental enamel color after fixed orthodontic therapy using two types of protectors to prevent white spot lesions (A prospective clinical study) - Yasir R Allabban (College of Dentistry/ University of Baghdad, 2020)
Background: The aim of this study is to evaluate the color change ∆E of the dental enamel following treatment with 2 kinds of protector (icon infiltrant, clinpro varnish) before fixed orthodontic treatment to avoid the possible white spot lesions. Materials and Methods: Fifty four subjects treated with fixed appliances were divided into 3 groups: the 1st group was control, while the 2nd and 3rd groups were treated with icon infiltrant and clinpro varnish before bonding procedure, respectively. Color parameters (L,a,b) were recorded for the middle and gingival thirds before and after bonding procedure to get the ∆E of each group. Results: One-way ANOVA test showed a non-significant difference in ∆E between the 3 groups at p value <0.05, while there were highly significant differences in value of ∆E between middle thirds and the gingival thirds in all groups. Conclusion: The icon infiltrant and clinpro varnish have no effect on color of the enamel when used before the bonding procedure. Color change ∆E occurring in middle third is higher than that of the gingival third. Keywords: Color change, protector, white spot lesions